If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9z + 15 + -2z = 0 Reorder the terms: 15 + 9z + -2z = 0 Combine like terms: 9z + -2z = 7z 15 + 7z = 0 Solving 15 + 7z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 7z = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 7z = 0 + -15 7z = 0 + -15 Combine like terms: 0 + -15 = -15 7z = -15 Divide each side by '7'. z = -2.142857143 Simplifying z = -2.142857143
| -3(1+m)=-10-2m | | 8x^3-3x^2+16x-6=0 | | (4x-3)(2x+5)-1=20x-4(2x+1)(2-x)+6 | | 7b-14=3(-2+b) | | 14x+16=-12 | | 6(z-2)=3z-8+3z | | -8n-28=-4(n+1) | | -4n+2n+16=n+7 | | 0.2x=0.1-0.7x | | -3x^3-15x^2-12x=0 | | 3x-14+5x=8x+10 | | 6x=5x+18 | | -8m=1-7m+7 | | -39+6k=5-5(2-8k) | | -39-6x=-3(7x+3) | | 10-7n=-2(5n+7) | | x/6-(-10)=3 | | b-8=36 | | 5x-465=0 | | a*8=b*8-c | | x^2+21x+12=9x+1 | | y=(x+5)2 | | -8(-4+7x)+8x=-17+x | | 10x=300 | | 5(2x+4)=-70 | | -6(9-6x)=10(9+3x) | | 4x^2-11x+15=2x+6 | | 2(a-9)+10=2-(10-10a) | | 2x^3+56x^2+54x=0 | | 2w+21=6w-7 | | -7(a-5)=-8a+29 | | 4x^2+11x+15=2x+6 |